(untitled) (Huellas, 2015)
A phenomenon characteristic of metropolitan areas is reproduced in intermediate cities: differential valuation of the urban land where some areas are articulated and highly valued, while others are marginalized, badly structured and dysfunctional. The government of the province has the primary function of creating mechanisms to guarantee access to the urban land to social groups with lower benefits. Decisions made with regard to planning matters when establishing criteria for the location of social housing have caused processes of exclusion and imbalance in the urban structure, as well as having marked the tendency of urban growth in the town. Nowadays, the municipality of Santa Rosa is working, on the one hand, on the design of legislation aimed at the social production of the habitat from a comprehensive development, and on the other hand, it is in a process of revision of the urban code with the aim of incorporating lands to expand the urban area, in response to the demand of vacant plots. The aim of this work is to analyze the implementation of public policies in order to explain the generation of “multi-territorialities”, based on the entitlement of the citizens to the town or on urban growth.